2007
DOI: 10.1152/ajplung.00256.2006
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical markers of alveolar epithelial barrier dysfunction in perfused human lungs

Abstract: Frank JA, Briot R, Lee JW, Ishizaka A, Uchida T, Matthay MA. Physiological and biochemical markers of alveolar epithelial barrier dysfunction in perfused human lungs. Am J Physiol Lung Cell Mol Physiol 293: L52-L59, 2007. First published March 9, 2007; doi:10.1152/ajplung.00256.2006.-To study air space fluid clearance (AFC) under conditions that resemble the clinical setting of pulmonary edema in patients, we developed a new perfused human lung preparation. We measured AFC in 20 human lungs rejected for tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 42 publications
6
96
0
Order By: Relevance
“…Furthermore, in a separate study, lungs rejected for transplant with measurable basal and stimulated fluid clearance had mean basal AFC rates of 19 Ϯ 10%/h and mean stimulated (terbutaline) AFC of 43 Ϯ 13%/h (17). Lungs were included in this study if the lung demonstrated impaired AFC, with lungs included if baseline AFC was Ͻ10%/h and cold ischemia time Ͻ48 h. Based on this criterion, from July 2011 to June 2012, ϳ50% of rejected lungs were eligible.…”
Section: Methodsmentioning
confidence: 91%
“…Furthermore, in a separate study, lungs rejected for transplant with measurable basal and stimulated fluid clearance had mean basal AFC rates of 19 Ϯ 10%/h and mean stimulated (terbutaline) AFC of 43 Ϯ 13%/h (17). Lungs were included in this study if the lung demonstrated impaired AFC, with lungs included if baseline AFC was Ͻ10%/h and cold ischemia time Ͻ48 h. Based on this criterion, from July 2011 to June 2012, ϳ50% of rejected lungs were eligible.…”
Section: Methodsmentioning
confidence: 91%
“…For the experimental preparation (Figure 4), lungs were continuously perfused at 37°C with DMEM containing 5% albumin and 16% (v/v) fresh whole human blood by roller pump to maintain a pulmonary artery pressure of 10-12 mmHg with passive drainage of perfusate through an open left atrium into a reservoir for recirculation (53,54). Lungs were inflated to continuous positive airway pressure (CPAP) of 10 mmHg with either 95% O 2 (FiO 2 = 0.95) or 21% O 2 (FiO 2 = 0.21), and a recruitment maneuver with sustained inflation to 25 mmHg was performed prior to the experiment (53,54). The lung was suspended from a mass transducer for continuous measurement of lung weight as an index of pulmonary edema formation.…”
Section: Methodsmentioning
confidence: 99%
“…15 In more recent work, we adapted our ex vivo perfused human lung preparation for studies of ALI to test the effects of MSC therapy. 16 In this study, the right middle lobe was injured with intraalveolar endotoxin (6 mg), resulting in a sharp increase in lung endothelial and epithelial permeability to protein leading to pulmonary edema and a loss of the normal capacity of the alveolar epithelium to remove alveolar fl uid. 17 When the lung was treated 1 h after instilla- .…”
Section: Preclinical Studiesmentioning
confidence: 99%